Poetics of the Elsewhere Notes on Peter Sloterdijk and the Question of Utopia (Altre Modernità, 2019)
The paper explores the question of utopia in the work of Peter Sloterdijk from a narratological and meta-poetic perspective. The analysis focuses on a new text by the German thinker, published in 2018 as an afterword to the German edition of Thomas More’s Utopia, translated from the original Latin by Jacques Laager. In the paper I will present the text, contextualizing it in the complexity of Sloterdijk’s work. I will examine some of its thematical and stylistic features, which disclose the in-terplay between storytelling, space, and writing in the construction processes of the concepts of sub-jectivity, otherness, and community. Moreover, such an interplay allows to read the space of writing as a place of meta-reflection through which the author, by rethinking and rewriting the (hi)story of mankind from different conceptual prisms, rethinks and rereads also the peregrination of a new philosophical subject in the landscape of writing.
Keywords: Peter Sloterdijk; Thomas More; Utopia; Utopian Literature; Carl Sagan